Humpback whale (Megaptera novaeangliae) occurrence in the Mediterranean Sea - Frantzis , A.; Nikolaou, O.; Bompar , J. M.; Cammedda , A. (J. Cetacean Res. Manage., 2023)
Humpback whales were considered extremely rare in the Mediterranean Sea until recently. Only two confirmed records were known from a period of more than 100 years and both were from the western basin. However, nine new observations spread across both Mediterranean basins have been recorded since 1990. This increase in numbers and range during a relatively short period of time seems to be a new, growing trend, suggesting that the occurrence of humpback whales in the Mediterranean Sea is no longer accidental, but occasional. It coincides with the recovery of some stocks of the expanding North Atlantic population after their depletion during a long period of whaling. The true reason behind increased humpback whale entries in the Mediterranean Sea and their exact origin cannot be known until new occurrences are properly photo-identified and sampled genetically.